Reasonability and the Linguistic Division of Labor in Institutional Work - Schildt, Henri A.; Mantere, Saku; Vaara, Eero (Journal of management inquiry, 2011)
We examine institutional work from a discursive perspective and argue that reasonability, the existence of acceptable justifying reasons for beliefs and practices, is a key part of legitimation. Drawing on philosophy of language, we maintain that institutional work takes place in the context of ‘space of reasons’ determined by widely held assumptions about what is reasonable and what is not. We argue that reasonability provides the main contextual constraint of institutional work, its major outcome, and a key trigger for actors to engage in it. We draw on Hilary Putnam’s concept ‘division of linguistic labor’ to highlight the specialized distribution of knowledge and authority in defining valid ways of reasoning. In this view, individuals use institutionalized vocabularies to reason about their choices and understand their context with limited understanding of how and why these structures have become what they are. We highlight the need to understand how professions and other actors establish and maintain the criteria of reasoning in various areas of expertise through discursive institutional work.